The Influence of Occupational Health and Safety (OHS) Knowledge and Employee Conditions on Safety Attitude at PT AItrak 1978 - Juwita Septriasa; Totok Sulistyo; Rahmat Bangun Giarto (Civil Engineering Dept, Balikpapan State Polytechnics, 2024)
Knowledge of Occupational Safety and Health (K3) is one of the important aspects forworkers in working on projects so as to minimize an accident. K3 knowledge also plays a role in the safety attitude of workers, but from observations there are still workers who do not use Personal Protective Equipment (PPE) such as not using masks and helmets.The purpose of this study was to determine knowledge (K3) and Safety Attitude and to determine the effect of knowledge (K3) and employee conditions on the Safety Attitude ofworkers at PT Altrak 1978.The results of the research on knowledge of K3 and Safety Attitude using descriptive statistical analysis are the results of the variable (X1) anaverage of 4.61% the result of the variable (Y) an average of 4.68 which means that it isincluded in the very high category. Analysis of the OHS knowledge questionnaire variable there are 18 respondents (61%) who choose strongly agree and 12 respondents (39%) whochoose agree and the analysis of the Safety Attitude variable questionnaire variable there are20 respondents (69%) who choose strongly agree and 10 respondents (31 %) who chose toagree, so it can be concluded that the knowledge of K3 and Safety Attitude of workers is verygood.